2014
DOI: 10.1539/joh.13-0244-cs
|View full text |Cite
|
Sign up to set email alerts
|

Allergic Contact Dermatitis from Two‐component Acrylic Resin in a Manicurist and a Dental Hygienist

Abstract: Allergic Contact Dermatitis from Twocomponent Acrylic Resin in a Manicurist and a Dental Hygienist: Keiko MINAMOTO, Department of Environmental and Preventive Medicine, Faculty of Life Sciences, Kumamoto University— Backgrounds Two‐component acrylic resin used in nail art and dentistry can cause allergic contact dermatitis (ACD), but only a few reports from Japan have been published. Cases A 35‐year‐old female manicurist (case 1) and 30‐year‐old female dental hygienist (case 2) were diagnosed with ACD caused b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 19 publications
0
14
0
1
Order By: Relevance
“…A number of studies appeared to meet the inclusion criteria at first, [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] but they had to be omitted because they focused on a population that was inappropriate for this review. Case reports [38][39][40][41] and case series [42][43][44][45][46][47] were not included in the actual review, but compiled and extracted as supplemental information in case they were relevant in terms of including hairdressers and beauticians. We arrived at a final number of six papers after excluding publications that were extraneous to this review.…”
Section: Study Selection and Study Characteristicsmentioning
confidence: 99%
“…A number of studies appeared to meet the inclusion criteria at first, [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] but they had to be omitted because they focused on a population that was inappropriate for this review. Case reports [38][39][40][41] and case series [42][43][44][45][46][47] were not included in the actual review, but compiled and extracted as supplemental information in case they were relevant in terms of including hairdressers and beauticians. We arrived at a final number of six papers after excluding publications that were extraneous to this review.…”
Section: Study Selection and Study Characteristicsmentioning
confidence: 99%
“…Although acrylates have been well characterized to induce irritant and ACD in other industries such as painting, printing, and health care, their use in the cosmetology sector is increasing. 38 In a seven-year study with 2,263 patients evaluated for dermatitis caused by acrylates, cosmetologists working with artificial nails were identified as 80% of all occupational cases of ACD. 39…”
Section: Cosmetologymentioning
confidence: 99%
“…Mikov et al (89) showed that not all reactions are due to latex, but in some cases, acrylate macromolecules can cross through latex, resulting in an allergic reaction. The reaction to acrylics is due to direct contact with the skin or mucosa and is attributed mostly to the non-polymerized monomers in these materials (94)(95). The monomers can cause clinical cases of dermatitis and even neuropathies in the fingers or hands (56,59).…”
Section: Discussionmentioning
confidence: 99%